PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD SWASTA METHODIST SUNGAI BAKAU KECAMATAN SINABOI - ', Sondang; ', Lazim. N; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This Research is background by lowering of result of learning IPS of student of class of V SD of Private Sector of Methodist of River of Mangrove of Subdistrict Sinaboi, with the class mean 66,82. While Complete Criterion value Minimize the (KKM) IPS is 75. Among/Between student amounting to 22 people only 8 one who reach the KKM, while 14 people do not reach the KKM. This Research represent the Research of Class Action (PTK) done/conducted aim to to increase result of learning IPS of Student of class of V SD of Private Sector of Methodist of River of Mangrove of Subdistrict Sinaboi with the applying model the direct study. Instrument of data collecting of at this skripsi is activity sheet learn and student and also result of learning. This Skripsi present the data of result of learning obtained from mean of result of learning before action 66,82 mounting 12,04 becoming 78,86 at cycle I. At cycle II mount to become 9,09 with the mean 87,95. Activity learn at first cycle I meeting obtain;get the percentage of equal to 65% with the good category, at second meeting of cycle I experience of the improvement with the percentage 80% good category. Hereinafter first cycle II meeting of activity learn also experience of the improvement with the percentage 90% good category very and at second meeting of cycle II 95% category very goodness. Student activity of at first cycle I meeting obtain;get the percentage 55% category enough, at second meeting experience of the improvement with the percentage 65% good category. At this cycle is student start to comprehend the study activity by applying model the direct study marked with the student activity of at, first cycle II meeting of student activity also experience of the improvement with the percentage 80% good category, and at second meeting of cycle II 90% category very goodness. Result of research in class of V SD of Private Sector of Methodist of River of Mangrove of Subdistrict Sinaboi prove that applying model the direct study can improve the result learn the student of class of V SD of Private Sector of Methodist of River of Mangrove of Subdistrict Sinaboi.Keyword : Model the direct pembelajan, result of learning IPS, PTK2